CONTRACT FARMING AND FRITOLAY’S MODEL OF CONTRACT FARMING FOR POTATO - Chaturvedi, Rahul (Potato Journal, 2013)
Farming is the age-old means of lively hood for millions of Indians. However, there have been few systems/ models in which farmers are assured of a market for their produce, leave alone a remunerative price. Farmers have on occasion had to throw their produce away for want of buyers. On the other side, agriculture based and food industries require timely and adequate inputs of good quality agriculture produce. This underlying paradox of the Indian agriculture scenario has given birth to the concept of Contract Farming, which promises to provide a proper linkage between the ‘farms and market’. Contract farming can indeed be a vehicle for the modernization of agriculture in India. It can be a means to bring about a market focus to Indian farming.